An Integrated Model to Predict Cheating on Online Exam Among Accounting Students: Does Islamic Religiosity Matter? - Muamar Nur Kholid; Fierda Ayu Apralia Diptasary; Yunice Karina Tumewang (Jurnal Reviu Akuntansi dan Keuangan, 2021)
The purpose of this study is to empirically examine a model of cheating behavior of accounting students on online exams to determine the factors that influence the intention of accounting students to cheat on online exams. Based on the literature review, the factors that influence the intention of accounting students to cheat on online exams are identified in the scope of Ethics Theory (deontological and teleological evaluation), Theory of Planned Behavior, and Islamic Religiosity. The data were obtained from an online questionnaire survey distributed to Accounting students. The data were analyzed using PLS - SEM. The results of data analysis show that perceived behavioral control, subjective norm, attitude, and perceived benefits have a positive effect on the intention to cheat on online exams. Furthermore, the results show that Islamic religiosity can be a deterrent factor for accounting students for cheating on online exams. The model proposed in this study will help accounting lecturers in universities to be able to minimize or to prevent cheating among accounting students on online exams.